Comparative Analysis of Russia’s Alliance-Formation Strategies in the Middle East - M. A. Suchkov; M. S. Khodynskaya-Golenischeva (Сравнительная политика, 2020)
Contemporary history of the Middle East has seen at least four periods of active inter-state alliance formation – three of which led by the United States. The return of Russia to the Middle East has helped shape new alliances and coalitions. Unlike the American “philosophy” of alliance formation underpinned by the imperative for a comprehensive politicomilitary presence as well as prevention of, first, Soviet and then, Iranian regional expansion, the Russian model is oriented toward the players, cooperation with which could solve a current or a potential crisis at a specific time period. Coupled with consistent and pragmatic foreign policy course, it was nontrivial strategies for flexible alliance-formation that enabled Moscow to establish itself as one of the leading player in the turbulent region as well as a responsible global power. At the same time, the comparative analysis of the Russian campaign in Syria and Moscow’s relations with key states in the region shows that Russia has been exercising elements of at least three alliance-formation strategies.